GAMMA-IRRADIATION EFFECTS ON FREE RADICALS INDUCTION, BIOACTIVE CONSTITUENTS AND TOXICITY OF HOUTTUYNIA CORDATA THUNB LEAVES - Thongphasuk, Piyanut; Thongphasuk, Jarunee (Interprofessional Journal of Health Sciences, 2023)
Gamma irradiation is a method utilized to improve the safety in usages of medicinal herbs by inactivation of microorganisms. However, irradiation may also affect bioactive compounds present inof the irradiated herbs, the objective of this research thus is to study the effects of γ-irradiation (10 and 25 kGy) on free radicals induction, bioactive constituents and toxicity of Houttuynia cordata Thunb leaves. Electron paramagnetic resonance spectroscopy (EPR) and GC-MS were used to determine free radicals induction and changes of bioactive constituents present in volatile oils, respectively. Its total phenolic content and antioxidant activity were investigated using Folin-Ciocalteu assay and DPPH radical scavenging assay, respectively. Toxic effect was detected with Toxi-chromo test in E. coli. The results showed that irradiation at the doses of 10 and 25 kGy significantly (P < 0.05) increased the free radicals induction. However, its bioactive constituents in volatile oils, total phenolic content, antioxidant activity and toxicity in E. coli were not significantly (P > 0.05) affected by the irradiation doses. In conclusion, the data suggest that the gamma irradiation doses up to 25 kGy could be safely used to pasteurize dried Houttuynia cordata Thunb leaves.